PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE PEMBELAJARAN MIND MAPPING DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Febryanti Febryanti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
This research is a class action (classroom action research), which aims to determine the mathematical learning outcome of students through a learning method mind mapping approach Contextual Teaching and Learning (CTL). Subjects in this study were VIII2 grade students of SMP Negeri 2 Polewali as many as 32 students. This study consisted of two cycles, with each cycle lasts for 4 meetings which is 3 times the meeting for the implementation of measures and one-off meeting for the end of the test cycle. The result showed that the results of learning mathematics increased through learning methods CTL mind mapping approach. It is shown from mastery learning students from the first cycle to the second cycle, the first cycle ketuntasannya reached 78.12% and the second cycle of 96.87%. Activities of students from the first cycle to the second cycle also increased.